Upsetness, press and citizenship within the context of mining production in northern Chile - Yáñez-Duamante, Constanza (2016)
This research addresses social representations through journalistic discourses and their mediated constructions with regard to the public discomfort of organized citizens in response to the impact of mineral production consequences in their quality of lives. The main objective seeks to understand processes of news construction and representations that mass media reproduce through verbo-visual discourses of ‘difference’ coming from the citizen movement named “What would it be of Chile without Calama”. In order to achieve this goal, a critical and complex analysis on the journalistic discourse is carried out, with the purpose of discovering how the newspapers represent reality of those speeches that are seen as ‘different’ (periphery), considering their sociopolitical distance with the ‘discourses of authority’ (centre).